The role of orphanin FQ/nociceptin in neuroplasticity: relationship to stress, anxiety and neuroinflammation - Mallimo, Elyse M.; Kusnecov, Alexander W. (Frontiers in Cellular Neuroscience, 2013)
The neuropeptide, orphanin FQ/nociceptin (OFQ/N or simply, nociceptin), is expressed in both neuronal and nonneuronal tissue, including the immune system. In the brain, OFQ/N has been investigated in relation to stress, anxiety, learning and memory, and addiction. More recently, it has also been found that OFQ/N influences glial cell functions, including oligodendrocytes, astrocytes and microglial cells. However, this latter research is relatively small, but potentially important, when observations regarding the relationship of OFQ/N to stress and emotional functions is taken into consideration and integrated with the growing evidence for its involvement in cells that mediate inflammatory events. This review will first provide an overview and understanding of how OFQ/N has been implicated in the HPA axis response to stress, followed by an understanding of its influence on natural and learned anxiety-like behavior. What emerges from an examination of the literature is a neuropeptide that appears to counteract anxiogenic influences, but paradoxically, without attenuating HPA axis responses generated in response to stress. Studies utilized both central administration of OFQ/N, which was shown to activate the HPA axis, as well as antagonism of NOP-R, the OFQ/N receptor. In contrast, antagonist or transgenic OFQ/N or NOP-R knockout studies, showed augmentation of HPA axis responses to stress, suggesting that OFQ/N may be needed to control the magnitude of the HPA axis response to stress. Investigations of behavior in standard exploratory tests of anxiogenic behavior (eg., elevated plus maze) or learned fear responses have suggested that OFQ/N is needed to attenuate fear or anxiety-like behavior. However, some discrepant observations, in particular, those that involve appetitive behaviors, suggest a failure of NOP-R deletion to increase anxiety.